Clinical Outcomes from Unselected “Real-World” Patients with Long Coronary Lesion Receiving 40 mm Biodegradable Polymer Coated Sirolimus-Eluting Stent - Anurag Polavarapu; Raghava Sarma Polavarapu; Jayesh Prajapati; Kamlesh Thakkar; Asif Raheem; Tamanpreet Mayall; Ashok Thakkar (Scientifica)
Background. Long lesions being implanted with drug-eluting stents (DES) are associated with relatively high restenosis rates and higher incidences of adverse events. Objectives. We aimed to examine the safety and efficacy of the long (40 mm) biodegradable polymer coated Indolimus sirolimus-eluting stent (SES) in real-world patients with long coronary lesions. Methods. This study was observational, nonrandomized, retrospective, and carried out in real-world patients. A total of 258 patients were enrolled for the treatment of long coronary lesions, with 40 mm Indolimus. The primary endpoints in the study were incidence of major adverse cardiac events (MACE), a miscellany of cardiac death, myocardial infarction (MI), target lesion revascularization (TLR) or target vessel revascularization (TVR), and stent thrombosis (ST) up to 6-month follow-up. Results. The study population included higher proportion of males (74.4%) and average age was 53.2 ± 11.0 years. A total of 278 lesions were intervened successfully with 280 stents. The observed MACE at 6-month follow-up was 2.0%, which included 0.8% cardiac death and 1.2% MI. There were no TLR or TVR and ST observed during 6-month follow-up. Conclusions. The long (40 mm) Indolimus stent demonstrated low MACE rate and was proven to be safe and effective treatment for long lesions in “real-world” patients.